PERTUMBUHAN DAN HASIL TIGA TANAMAN TOMAT PADA CEKAMAN SALINITAS - Welianto Boboy (Politeknik Pertanian Negeri Kupang, 2012)
Growth and Yields of Three Tomato Plants In Salinity Stress. Salinity negatively affects to growth and yield of crops. It can be reduced by planting adaptive plants as a method to overcome. The research was to study the effect of saline water gradient to three cultivars of tomato in relation to growth and yields, and to determine the tolerance level of the 3 tomato cultivars grown in saline conditions. A split plot was used with three replications in each treatment.Â The main-plots were 3-levels saline water gradient: 0 dS.m-1 (control), 2.5 dS.m-1 (a low level), and 5.0 dS.m-1 (a moderate level). The sub-plots were three different tomato cultivars: Rempai, Royal and Permata. The result showed that saline water gradient (2.5 and 5.0 dS.m-1) reduced the growth and yield of the 3 experimental tomato cultivars.Â The decrease of growth and yields in Rempai was lower than two other cultivars, Royal and Permata, due to the slightingly and moderately saline water gradient. In salinity stress, Rempai was lower in the stress sensitivity indices, and higher in the stress tolerance and yield stability indices. It indicated that Rempai was more resistant than Permata and Royal against to salinity stress. Key words: tomato, salinity, growth, yield, resistance.